Distance Learning and Media Strategy Design Use of Distance Learning Media for Christian Religious Education for the Needs of Providing Alternative Classes for Christian Religious Education by Distance for Elementary School Students in Indonesia - Iskandar, Ferdinand; Tambunan, Daulat Marulitua (Journal of Ecohumanism, 2024)
This study highlights the importance of implementing learning strategies in Christian Religious Education and Character Education in elementary schools in Indonesia, particularly in the context of remote learning during the COVID-19 pandemic. The main issues addressed are limited technology access and the readiness of teachers and students to use online learning applications. The aim of the study is to identify effective learning strategies that can enhance students' understanding and performance in this subject. A qualitative research method with a case study approach was employed, involving interviews with teachers, observations of online classes, and curriculum document analysis. The study results indicate that blended learning strategies, combining online and offline instruction, are more effective than traditional approaches alone. Teachers who successfully integrate technology innovatively can create interactive and engaging learning environments. The conclusion of this study is that adapting learning strategies to pandemic conditions and providing adequate technological infrastructure support can facilitate a more efficient and effective teaching and learning process. This study recommends increasing technology training for teachers and ensuring equitable internet access to support the success of remote learning.